Spontaneous neonatal gastric perforation in a very preterm neonate - M. G., Kartheeka; Shenoi, Arvind; Rao, Nilesh Nikhilesh (International Journal of Contemporary Pediatrics, 2020)
Gastric perforation in neonates is a rare, serious and life-threatening problem. The precise aetiology is obscure in most cases. By virtue of its high mortality rate, it requires prompt recognition and surgical intervention. We report a case of gastric rupture in a very preterm/very low birth weight neonate with antenatal reversal of flow in umblical artery.